AMC HETNET Macro and Femto Cell used 10 GHz for Drone Communication with SKE Method around Building Environment - Andrita Ceriana Eska; Ali Rizal Chaidir; Gramandha Wega Intyanto (Journal of Electrical, Electronic, Mechanical, Informatic and Social Applied Science, 2026)
Communication propagation between a drone and a HetNet (Heterogeneous Network) gNB (generalized Node B) in uplink conditions. The drone moves on a straight path between built-up environments. The communication frequency of 10 GHz can affect oksigen and water vapor at that frequency. Propagation of communication systems in a building environment can cause diffraction. The diffraction mechanism was modeled with Single Knife Edge (SKE) method. AMC (Adaptive Modulation and Coding) dynamically modifies the coding rate and modulation scheme according to signal quality. MCS (Modulation and Coding Scheme) consisting of QPSK, 16QAM, and 64QAM was used in AMC. Research analysis includes SNR values ​​on the drone path, coverage percentage, and MCS percentage. As a result of research for MCS 64QAM coderate 4/5 with Selection Combining (SC) between HetNet gNB macrocell and gNB femtocell, 64 nodes or 95.52% were obtained. The communication coverage was obtained using MCS for drone communication on this route.